2013
DOI: 10.2337/db11-1740
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Variation in Vascular and Metabolic Function in Diet-Induced Obesity

Abstract: Circadian rhythms are integral to the normal functioning of numerous physiological processes. Evidence from human and mouse studies suggests that loss of rhythm occurs in obesity and cardiovascular disease and may be a neglected contributor to pathophysiology. Obesity has been shown to impair the circadian clock mechanism in liver and adipose tissue but its effect on cardiovascular tissues is unknown. We investigated the effect of diet-induced obesity in C57BL6J mice upon rhythmic transcription of clock genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 48 publications
(63 reference statements)
3
37
1
1
Order By: Relevance
“…Diet-induced obesity, from unrestricted access to a high fat diet, altered rhythms in circadian behaviors (activity and feeding), neuropeptides in the hypothalamus, and clock and metabolism gene expression in liver and adipose tissue of mice (Kohsaka et al 2007). Other studies have reported similar findings in response to diet-induced obesity in highly metabolic tissues (Bravo, et al 2014; Lizier, et al 2013; Pendergast, et al 2013; Prasai, et al 2013; Shi, et al 2013). Recent work by Sassone-Corsi and colleagues also shows that a high fat diet disrupts normal circadian oscillations of the molecular clock and clock-controlled metabolites and transcripts in the liver (Eckel-Mahan, et al 2013); they propose that these high fat diet-mediated alterations in metabolism are linked to impaired CLOCK-BMAL1 chromatin recruitment and induction of peroxisome proliferator-activated receptor gamma (PPARγ)-mediated oscillations in noncyclic genes (Eckel-Mahan et al 2013).…”
Section: Cardiometabolic Consequences Of Disrupted Circadian Rhythmssupporting
confidence: 72%
“…Diet-induced obesity, from unrestricted access to a high fat diet, altered rhythms in circadian behaviors (activity and feeding), neuropeptides in the hypothalamus, and clock and metabolism gene expression in liver and adipose tissue of mice (Kohsaka et al 2007). Other studies have reported similar findings in response to diet-induced obesity in highly metabolic tissues (Bravo, et al 2014; Lizier, et al 2013; Pendergast, et al 2013; Prasai, et al 2013; Shi, et al 2013). Recent work by Sassone-Corsi and colleagues also shows that a high fat diet disrupts normal circadian oscillations of the molecular clock and clock-controlled metabolites and transcripts in the liver (Eckel-Mahan, et al 2013); they propose that these high fat diet-mediated alterations in metabolism are linked to impaired CLOCK-BMAL1 chromatin recruitment and induction of peroxisome proliferator-activated receptor gamma (PPARγ)-mediated oscillations in noncyclic genes (Eckel-Mahan et al 2013).…”
Section: Cardiometabolic Consequences Of Disrupted Circadian Rhythmssupporting
confidence: 72%
“…F-values in the two-way ANOVA are frequently used to assess variances of genes in circadian rhythm [25,26]. Student's t-test was used to compare weights of body tissues and protein concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, intrauterine hyperglycemia is not only associated with increased perinatal morbidity and mortality, but also with increased lifelong risk for the exposed offspring of obesity, metabolic and cardiovascular diseases, and earlier development of T2DM 27,28. Disruption of the circadian rhythm occurs in obesity, diabetes, and cardiovascular disease and is another factor that increases risk for diabetes 29. Transcriptional alterations of the circadian locomotor output cycles kaput (CLOCK) genes in metabolic tissues lead to blunting of rhythms of glucose tolerance and insulin sensitivity 30.…”
Section: Risk Factors For the Progression To Diabetes And Screeningmentioning
confidence: 99%